Significance of stroma in biology of oral squamous cell carcinoma. Issue 1 (January 2018) - Vucicevic Boras, Vanja; Fucic, Aleksandra; Virag, Mihajlo; Gabric, Dragana; Blivajs, Igor; Tomasovic-Loncaric, Cedna; Rakusic, Zoran; Bisof, Vesna; Novere, Nicolas Le; Velimir Vrdoljak, Danko
The worldwide annual incidence of oral squamous cell carcinoma (OSCC) is over 300, 000 cases with a mortality rate of 48%. This cancer type accounts for 90% of all oral cancers, with the highest incidence in men over 50 years of age. A significantly increased risk of developing OSCC exists among smokers and people who consume alcohol daily. OSCC is an aggressive cancer that metastasizes rapidly. Despite the development of new therapies in the treatment of OSCC, no significant increase in 5-year survival has been recorded in the past decades. The latest research suggests focus should be put on examining tumor stroma activation within OSCC, as the stroma may contain cells that can produce signal molecules and a microenvironment crucial for the development of metastases. The aim of this review is to provide an insight into the factors that activate OSCC stroma and hence faciliate neoplastic progression. It is based on the currently available data on the role and interaction between metalloproteinases, cytokines, growth factors, hypoxia factor and extracellular adhesion proteins in the stroma of OSCC and neoplastic cells. Their interplay is additionally presented using the Systems Biology Graphical Notation in order to sublimate the collected knowledge and enable the more efficient recognition of possible new biomarkers in the diagnostics and follow-up of OSCC or in finding new therapeutic targets.